6+36÷4-3×3
in Bodmas will we solve that sum?
Answers
Answered by
3
Hola there,
Given => 6 + 36 ÷ 4 - 3 × 3
If we apply BORDMAS in this equation we will get following results.
=> 6 + 36 ÷ 4 - 3 × 3
=> 6 + 9 - 3 × 3
=> 6 + 9 - 9
=> 6. ...Ans
Hope this helps...:)
Given => 6 + 36 ÷ 4 - 3 × 3
If we apply BORDMAS in this equation we will get following results.
=> 6 + 36 ÷ 4 - 3 × 3
=> 6 + 9 - 3 × 3
=> 6 + 9 - 9
=> 6. ...Ans
Hope this helps...:)
Answered by
4
hope this helps you ☺☺
Attachments:
![](https://hi-static.z-dn.net/files/d9a/a4e9edd82499fa82ac7e4b15068f50e5.jpg)
bhumipotwar:
but its answer is coming 3
Similar questions